2022
DOI: 10.1002/ece3.9338
|View full text |Cite
|
Sign up to set email alerts
|

Diverse diets and low‐fiber, low‐tannin foraging preferences: Foraging criteria of Tibetan macaques (Macaca thibetana) at low altitude in Huangshan

Abstract: Nutrient composition and food availability determine food choices and foraging strategies of animals, while altitude and geographical location affect species distribution and food availability. Tibetan macaques ( Macaca thibetana ) have sophisticated foraging strategies as the largest species in Macaca . They are important in understanding the ecological evolution of the entire genus. However, the mechanism of food selection in Tibetan macaques at low altitudes rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Furthermore, Cui et al [55,59] were able to rule out other constraints as determinants of the observed pattern of intake, such as constraints on the amounts of food available across study years (i.e. quantitative constraint), or owing to inter-annual variation in non-nutrient substances, such as fibre and/or tannin, which can influence dietary intakes in primates [68,69], including some macaques [70]. This was achieved by establishing that lactating females ate substantially more food and macronutrients than non-lactating adult monkeys, thus showing that the pattern of macronutrient intake shown by non-lactating monkeys was not owing to limited availability of food.…”
Section: (B) Taihangshan Rhesus Macaquesmentioning
confidence: 99%
“…Furthermore, Cui et al [55,59] were able to rule out other constraints as determinants of the observed pattern of intake, such as constraints on the amounts of food available across study years (i.e. quantitative constraint), or owing to inter-annual variation in non-nutrient substances, such as fibre and/or tannin, which can influence dietary intakes in primates [68,69], including some macaques [70]. This was achieved by establishing that lactating females ate substantially more food and macronutrients than non-lactating adult monkeys, thus showing that the pattern of macronutrient intake shown by non-lactating monkeys was not owing to limited availability of food.…”
Section: (B) Taihangshan Rhesus Macaquesmentioning
confidence: 99%